Quantum-based modeling implies that bidentate Arg89-substrate binding enhances serine/threonine protein phosphatase-2A(PPP2R5D/PPP2R1A/PPP2CA)-mediated dephosphorylation - Salter, E. Alan; Wierzbicki, Andrzej; Honkanen, Richard E.; Swingle, Mark R. (Frontiers in Cell and Developmental Biology, 2023)
PP2A-serine/threonine protein phosphatases function as heterotrimeric holoenzymes, composed of a common scaffold (A-subunit encoded by PPP2R1A/PPP2R1B), a common catalytic (C-subunit encoded by PPP2CA/PPP2CB), and one of many variable regulatory (B) subunits. The site of phosphoprotein phosphatase (PPP) hydrolysis features a bimetal system (M1/M2), an associated bridge hydroxide [W1(OH−)], and a highly-conserved core sequence. In the presumptive common mechanism, the phosphoprotein’s seryl/threonyl phosphate coordinates the M1/M2 system, W1(OH−) attacks the central P atom, rupturing the antipodal bond, and simultaneously, a histidine/aspartate tandem protonates the exiting seryl/threonyl alkoxide. Based on studies of PPP5C, a conserved arginine proximal to M1 is also expected to bind the substrate’s phosphate group in a bidentate fashion. However, in PP2A isozymes, the role of the arginine (Arg89) in hydrolysis is not clear because two independent structures for PP2A(PPP2R5C) and PP2A(PPP2R5D) show that Arg89 engages in a weak salt bridge at the B:C interface. These observations raise the question of whether hydrolysis proceeds with or without direct involvement of Arg89. The interaction of Arg89 with B:Glu198 in PP2A(PPP2R5D) is significant because the pathogenic E198K variant of B56δ is associated with irregular protein phosphorylation levels and consequent developmental disorders (Jordan’s Syndrome; OMIM #616355). In this study, we perform quantum-based hybrid [ONIOM(UB3LYP/6-31G(d):UPM7)] calculations on 39-residue models of the PP2A(PPP2R5D)/pSer (phosphoserine) system to estimate activation barriers for hydrolysis in the presence of bidentate Arg89-substrate binding and when Arg89 is otherwise engaged in the salt-bridge interaction. Our solvation-corrected results yield ΔH‡ ≈ ΔE‡ = +15.5 kcal/mol for the former case, versus +18.8 kcal/mol for the latter, indicating that bidentate Arg89-substrate binding is critical for optimal catalytic function of the enzyme. We speculate that PP2A(PPP2R5D) activity is suppressed by B:Glu198 sequestration of C:Arg89 under native conditions, whereas the PP2A(PPP2R5D)-holoenzyme containing the E198K variant has a positively-charged lysine in this position that alters normal function.